2019
DOI: 10.1080/23311916.2019.1565630
|View full text |Cite
|
Sign up to set email alerts
|

Agent-based distributed manufacturing scheduling: an ontological approach

Abstract: The purpose of this paper is the need for self-sequencing operation plans in autonomous agents. These allow resolution of combinatorial optimisation of a global schedule, which consists of the fixed process plan jobs and which requires operations offered by manufacturers. The proposed agent-based approach was adapted from the bio-inspired metaheuristic-particle swarm optimisation (PSO), where agents move towards the schedule with the best global makespan. The research has achieved a novel ontology-based optimi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…The distributed management paradigm is well-suited for permitting the decomposition of management problems, which may arise in the scope of extended, agile, and virtual production systems, usually characterized by higher levels of complexity associated with its underlying networked organization [7,40,43,44,46,96,102].…”
Section: Results Analysis and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The distributed management paradigm is well-suited for permitting the decomposition of management problems, which may arise in the scope of extended, agile, and virtual production systems, usually characterized by higher levels of complexity associated with its underlying networked organization [7,40,43,44,46,96,102].…”
Section: Results Analysis and Discussionmentioning
confidence: 99%
“…Saeidlou et al in 2019 [43] propose a cooperative system to perform distributed manufacturing scheduling, based on a set of rules considered to be most relevant, which are integrated through their proposed cooperative system, through an agent-based decision support system that, according to the authors, enables them to find near-optimal solutions within a reasonable computational time.…”
Section: Global Resources Management In the Industry 40mentioning
confidence: 99%
“…There are different kinds of approaches that can be used for establishing production schedules, varying from enumerative algorithms to the application of simple priority rules. Moreover, these approaches can be based on pure mathematical programming models or use simulation technique among other approaches [5], for instance, based on multi-agents, among others [18,24,[37][38][39].…”
Section: Scheduling Problems and Solving Approachesmentioning
confidence: 99%
“…As discussed in the literature, systems of this nature requiring problem-solving capability need improvement using optimisation alorithms; these can also be multi-agent systems, or exchange models. The latter acknowledges the flow and development of information as opposed to the optimisation model which addresses the agents' objective functions (Nedic & Ozdaglar, 2009;Saeidlou et al, 2019b). Previous work by the authors has demonstrated encouraging findings regarding decentralised GA optimisation acquired through the use of REPAST (Jules & Saadat, 2017).…”
Section: Optimisation Of a Multi-agent Systemmentioning
confidence: 99%